Peran Penerapan Program Vaksinasi HPV dengan Optimalisasi Skrining dan Pengobatan Kanker Serviks sebagai Strategi Ambisius Penurunan Prevalensi Kanker Serviks di Negara-Negara Berkembang: Sebuah Tinjauan Pustaka - Meidina, Adinda Nezma; Putri, Yolanda Delia; Nugraha, M. Aditya; Fadhlan, Muhammad Muhadzdzab; Ramadhanti, Nafilah (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Background: Cervical cancer is the fourth most common type of cancer in women in the world, with 94% of total deaths worldwide occurring in developing countries in 2022. In response to this problem, WHO initiated a movement to eliminate cervical cancer, known as the 90-90 strategy, through implementing vaccination programs and optimizing screening and treatment for cervical cancer cases. This literature review aims to describe the role of these strategies in eliminating cervical cancer, especially in developing countries. Methods: Literature was searched using search sites such as Google Scholar, Science Direct, ResearchGate, and NCBI. Inclusion and exclusion criteria were used to eliminate unrelated literature to obtain 36 literature. Discussion: HPV vaccination has been proven to provide protective benefits in reducing the incidence of neoplastic lesions and shows a relatively decreasing trend in the group receiving the vaccine. Cervical screening plays a very important role in the early detection and therapy of precancer, which shows a trend in preventing cancer cases in the next 50 years. Modeling studies show that successful implementation of the WHO 90-70-90 intervention by 2030 will reduce the incidence of cervical cancer to 0.7 per 100,000 women and the death rate to 0.2 per 100,000 women in all developing countries. Conclusion: The implementation of the HPV vaccination program with the optimization of cervical cancer screening and treatment is believed to be a solution modality to reduce morbidity and mortality rates due to cervical cancer in the world, especially in developing countries.